2009
DOI: 10.2118/110542-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow in a Fractured Reservoir Using a Geomechanically Constrained Fault-Zone-Damage Model for Reservoir Simulation

Abstract: Secondary fractures and faults associated with larger, reservoir scale faults affect both permeability and permeability anisotropy and hence may play an important role in controlling the production behavior of a faulted reservoir. It is well known from geologic studies that there is a concentration of secondary fractures and faults in a damage zone adjacent to larger faults. Because there is usually inadequate data to incorporate damage zone fractures and faults into reservoir simulation models, in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 83 publications
0
29
0
Order By: Relevance
“…A few field studies have documented the influence of damage zones on production. For example, Paul et al [2009] report a study from the CS gas field (in the Timor gap between Australia and Indonesia) where it is only possible to explain large gas production rates by introducing spatially variable permeability anisotropy (in flow simulators) representative of damage zones present in the reservoir. Hennings et al [2012] report a case from the Suban gas field in SE Asia where the production from wells that sample damage zones is several times greater than those which do not traverse through damage zones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few field studies have documented the influence of damage zones on production. For example, Paul et al [2009] report a study from the CS gas field (in the Timor gap between Australia and Indonesia) where it is only possible to explain large gas production rates by introducing spatially variable permeability anisotropy (in flow simulators) representative of damage zones present in the reservoir. Hennings et al [2012] report a case from the Suban gas field in SE Asia where the production from wells that sample damage zones is several times greater than those which do not traverse through damage zones.…”
Section: Introductionmentioning
confidence: 99%
“…Fault damage zones may be created by various cumulative processes during or after fault formation, including Andersonian fracturing [Anderson, 1942;Scholz, 2002], early fault tip migration, fault tip linkage, cumulative fault wear with increasing displacement, (which are all quasi-static processes), and damage caused by dynamic rupture events [Rudnicki, 1980;Wilson et al, 2003;Paul et al, 2009]. These models are discussed by Mitchell and Faulkner [2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect is related to the fracture intensity decay from fault planes to the host rock: outcrop and subsurface studies showed that fracture intensity decrease while increasing distance from the fault plane to the host rock (Mitchell and Faulkner, 2009;Paul et al, 2007;Savage and Brodsky, 2011;Johri et al, 2014). This last topic is detailed in Section 4.3.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Because the degree of brittle deformation is significantly larger in the fault core (Andersson et al, 1991;Chester et al, 1993), the low fault-core permeability is governed by grain-scale (or smaller) matrix deformation of the fault rock (lowered further by clay gouge development). However, damage zones comprising higher permeability fractures and faults produce bulk permeability anisotropy related to higher permeabilities along the fault plane, thus enhancing fluid flow (Zhang and Sanderson, 1995;Paul et al, 2009). Lockner et al (2000) and Wibberley and Shimamoto (2003) reported experimentally measured permeabilities and showed that the permeability of core samples from the damage zone is several orders higher than that of samples taken from the fault core.…”
mentioning
confidence: 99%